Vocal fold cyst: A narrative review - Santosh Kumar Swain (Journal of Clinical and Scientific Research, 2024)
Vocal fold cysts are benign lesions of the larynx and affect both children and adults. The vocal fold cysts can be classified into two types such as mucous retention cysts and epidermoid cysts. Vocal overuse is often associated with the formation of the cyst on the vocal fold. The aetiological factor behind this lesion may be due to occupation. It frequently affects the people who use their voices professionally. The most common symptom of the vocal fold cyst is dysphonia or hoarseness of the voice, increased vocal effort, fatigue, strain and if the lesions are large enough, feeling of dyspnoea with phonation. If the size of the vocal cyst is very large, it may manifest life-threatening stridor. This lesion can create mental and emotional tension in daily life and affect the daily life of the patient. The vocal fold cyst is easily recognised and managed. Videostroboscopy is one of the most important techniques for the diagnosis of the vocal fold cyst. The vocal fold cyst rarely resolves entirely. The treatment options include speech therapy and transoral microlaryngeal surgery. Early diagnosis of the vocal fold cyst can lead to effective treatment and good vocal recovery. This article discusses the epidemiology, aetiopathogenesis, clinical features, diagnosis and present the treatment of vocal fold cysts.